Studies in natural products chemistry. - Rahman, Atta-ur-, 1942- (Studies in natural products chemistry, 2018)
Studies in Natural Products Chemistry, Volume 55 covers rapid developments in spectroscopic techniques, also presenting advances in high-throughput screening techniques, including the new potential to isolate and determine the structures and biological activity of natural products and their applications in the field of new drug development. This ongoing series covers the synthesis, testing and recording of the medicinal properties of natural products, providing cutting-edge accounts of fascinating developments in the isolation, structure elucidation, synthesis, biosynthesis and pharmacology of a diverse array of bioactive natural products.